The Absolute Priority Rule and the Firm's Investment Policy - Allan Schwartz (Washington University Law Quarterly, 1994)
This Article will focus on an aspect of the various reform schemes that Rasmussen notes but does not discuss in detail: each of these schemes increases the likelihood that the absolute priority rule will be strictly followed in bankruptcy. When absolute priority is strictly followed, senior claims are paid in full before junior claims get paid at all.
Keywords: Bankruptcy law; Corporation law; United States; Investments; Corporate governance; Bankruptcy